Evaluating The Impact Of Paramedics On Survival And Neurological Outcomes In Cardiac And Respiratory Arrest During Prehospital Care (The Review of Diabetic Studies, 2025)
Paramedics provide the earliest clinical actions during cardiac and respiratory arrest, directly influencing survival and neurological prognosis in the prehospital environment. This review evaluates the impact of core interventions—high-quality CPR delivery, early defibrillation, optimized oxygenation/ventilation, and structured post-ROSC care—on patient survival and brain-function outcomes. Evidence-based resuscitation practices endorsed by major guideline bodies demonstrate that minimizing hypoxia time and reducing CPR interruptions significantly improve circulation return and neurological recovery windows. Technology-enabled support such as mechanical compression and public access defibrillation programs further strengthens outcomes when combined with skilled paramedic performance. Neurological results are commonly assessed using validated clinical scales for post-arrest cerebral status and functional disability. Despite improvements, gaps remain in neurological tracking and standardized outcome reporting across EMS systems. Overall findings confirm that paramedic-led prehospital resuscitation improves survival and neurological outcomes when systematic clinical and operational protocols are applied, with strong implications for neuro-prognosis monitoring and EMS workflow optimization.